2022
DOI: 10.3389/fpubh.2022.1034925
|View full text |Cite
|
Sign up to set email alerts
|

Associations between professional identity and turnover intent in prehospital emergency physicians: The mediating effect of burnout

Abstract: ContextThe prehospital emergency system is essential for reducing mortality and disability in emergency patients. However, the high turnover rate of prehospital emergency physicians (PEPs) remains the most prominent problems in the prehospital emergency system. Turnover intent (TI) is predictive of actual turnover behavior; however, previous studies have mainly focused on sociodemographic factors and job characteristics, ignoring many other potential psychological factors, such as professional identity (PI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The motivation and tendency of in-service personnel to leave their current position is called turnover intention, which is a subjective factor that previously led to turnover behavior ( 10 ). Studies have found that turnover intention is associated with professional identity, work environment, burnout, job satisfaction, and stress ( 11 , 12 ). Scholars in China and abroad have shown through research on the current situation of medical staff that there is a significant positive correlation between burnout and turnover intention, namely, the higher the level of burnout among medical staff, the higher their turnover intention ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation and tendency of in-service personnel to leave their current position is called turnover intention, which is a subjective factor that previously led to turnover behavior ( 10 ). Studies have found that turnover intention is associated with professional identity, work environment, burnout, job satisfaction, and stress ( 11 , 12 ). Scholars in China and abroad have shown through research on the current situation of medical staff that there is a significant positive correlation between burnout and turnover intention, namely, the higher the level of burnout among medical staff, the higher their turnover intention ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although more and more research focuses on this relationship between work-family conflict and turnover intention among primary medical staff, there is limited research on the mediating role between work-family conflict and turnover intention. Especially in China, there is currently little research on the turnover intention of primary medical staff, and most studies focus solely on the turnover intention of doctors or nurses ( 12 , 16 , 17 , 22 , 23 , 35 , 37 ). In rare studies on the turnover intention of primary medical staff, burnout and turnover intention have been involved, but the relationship between work-family conflict and primary medical staff turnover intention has not been explored ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Categorical data are presented as percentages ( 41 ). Secondly, in order to explore differences in resilience scores among multiple sociodemographic variables, independent sample t-test ( 42 ) or one-way analysis of variance (ANOVA) was used. Pearson correlation analysis was used to determine the correlation between perceived social support, mindful self-care, and resilience.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 In addition, personal factors such as demographic characteristics, psychological capital, and emotional intelligence, also play crucial roles in burnout. 17,18 Burnout among nurses has been associated with various negative consequences, including mental and physical illnesses, 19 turnover intention, 20 decreased job satisfaction, 21 and worse quality of care, 22 which challenge both the individuals and healthcare institutions. Thus, predicting the burnout among nurses is very important for nursing management.…”
Section: Introductionmentioning
confidence: 99%